Kidney injury enhances renal G-CSF expression and modulates granulopoiesis and human neutrophil CD177 in vivo. (30th September 2019) - Volkmann, J; Schmitz, J; Nordlohne, J; Dong, L; Helmke, A; Sen, P; Immenschuh, S; Bernhardt, W M; Gwinner, W; Bräsen, J H; Schmitt, R; Haller, H; et al.
Summary: Kidney injury significantly increases overall mortality. Neutrophilic granulocytes (neutrophils) are the most abundant human blood leukocytes. They are characterized by a high turnover rate, chiefly controlled by granulocyte colony stimulating factor (G-CSF). The role of kidney injury and uremia in regulation of granulopoiesis has not been reported. Kidney transplantation, which inherently causes ischemia–reperfusion injury of the graft, elevated human neutrophil expression of the surface glycoprotein CD177. CD177 is among the most G-CSF-responsive neutrophil genes and reversibly increased on neutrophils of healthy donors who received recombinant G-CSF. In kidney graft recipients, a transient rise in neutrophil CD177 correlated with renal tubular epithelial G-CSF expression. In contrast, CD177 was unaltered in patients with chronic renal impairment and independent of renal replacement therapy. Under controlled conditions of experimental ischemia–reperfusion and unilateral ureteral obstruction injuries in mice, renal G-CSF mRNA and protein expression significantly increased and systemic neutrophilia developed. Human renal tubular epithelial cell G-CSF expression was promoted by hypoxia and proinflammatory cytokine interleukin 17A in vitro . Clinically, recipients of ABO blood group-incompatible kidney grafts developed a larger rise in neutrophil CD177. Their grafts are characterized by complement C4d deposition on the renal endothelium, even in the absence of rejection. Indeed, complement activation, but not hypoxia, induced primary human endothelial cell G-CSF expression. Our data demonstrate that kidney injury induces renal G-CSF expression and modulates granulopoiesis. They delineate differential G-CSF regulation in renal epithelium and endothelium. Altered granulopoiesis may contribute to the systemic impact of kidney injury. Graphical Abstract: